Decentralizing government and centralizing gender in Southern Africa: Lessons from the South African experience - Jo Beall (United Nations Research Institute for Social Development (UNRISD), 2005)
Decentralization is frequently presented as an important vehicle for increasing women's representation and political participation. However, the benefits for women of devolved local government are not always obvious. The paper starts from the premise that local government is in an ambiguous position. It is the part of the state that is located closest to the people and to organized civil society. As such it has the potential to engage more effectively with women who are often confined through their domestic responsibilities to public engagement close to home, but because of its closeness to society the local state can become too close to social institutions. In Africa, the latter can be deeply patriarchal, illustrated for example by the role of traditional authorities both in everyday life at the community level and in local government. When local government is impervious to progressive social change it may be an unreliable site for the pursuit of gender equity, particularly in contexts where women are making gains within the formal institutions of the state. As such it stands as a litmus test of not only democratic decentralisation but of engendered democracy more generally. These arguments are taken up in the context of an exploration of decentralization and local democracy in Southern Africa. An overview of some of the regional issues is provided through a study of Angola and Mozambique, which are discussed as two countries that have experienced sustained civil war, and Zimbabwe and Zambia that experience greater and lesser degrees of conflict in the context of economic stress and fragile states. The paper then explores in greater depth the case of South Africa, which has undergone a relatively stable transition from apartheid, accompanied by a commitment to gender inclusive politics and policy. Here it is demonstrated that even in a seemingly best-case scenario such as South Africa, engendered processes of local level democratization and service delivery are difficult to achieve. Two conclusions are drawn. The effective involvement of women in local governance is predicated both on the approach adopted by political parties and on how women are organized at the local level. However, even when women are effectively organized and represented locally, the close association between decentralization and neo-liberal policies serves to undermine the potential for gender-sensitive service delivery.
Keywords: 330